2021
DOI: 10.3390/app11136215
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Biochemical Composition and Physicochemical Properties of Apples Stored in Controlled Atmosphere Conditions

Abstract: Apples are an important component of the diet and are used in the food industry in the production of food products and beverages. The aim of the study was to determine the changes in the biochemical composition and physicochemical properties of apples stored in a controlled atmosphere. We studied the biochemical composition (sugars, ascorbic acid, soluble solids, and titratable acidity) and physicochemical properties (color coordinates, peel, and flesh firmness) in the apple samples before placing them in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…In this study, the sugar/acid ratio decreased in dried apple chip samples as follows: G1 (36.19) > S1 (33.33) > G2 (29.57) Iordănescu et al [53] reported TSS values ranging between 13.0 and 15.3 • Brix for 'Starkrimson' apples, between 10.6 and 14.2 • Brix for apples from the 'Florina' cultivar and 12.2-15.8 • Brix for 'Golden Delicious' apples. The total solids content for three apple cultivars determined by Egea et al [60] varied from 13.78 to 17.61%, while Butkeviciute et al [6] reported that the soluble solids content of ten different apple cultivars ranged between 12.40 and 14.00%.…”
Section: Ph Titratable Acidity and Total Solids Contentmentioning
confidence: 96%
See 4 more Smart Citations
“…In this study, the sugar/acid ratio decreased in dried apple chip samples as follows: G1 (36.19) > S1 (33.33) > G2 (29.57) Iordănescu et al [53] reported TSS values ranging between 13.0 and 15.3 • Brix for 'Starkrimson' apples, between 10.6 and 14.2 • Brix for apples from the 'Florina' cultivar and 12.2-15.8 • Brix for 'Golden Delicious' apples. The total solids content for three apple cultivars determined by Egea et al [60] varied from 13.78 to 17.61%, while Butkeviciute et al [6] reported that the soluble solids content of ten different apple cultivars ranged between 12.40 and 14.00%.…”
Section: Ph Titratable Acidity and Total Solids Contentmentioning
confidence: 96%
“…TA values are close to those obtained by Nour et al [59]: 0.30% for 'Golden Delicious', 0.20% for 'Florina' and 0.10% for 'Starkrimson'. Butkeviciute et al [6] reported a titratable acidity for other apple cultivars that varied between 0.24 and 0.61%. Titratable acidity values of dried apple chip samples are presented in Table 1.…”
Section: Ph Titratable Acidity and Total Solids Contentmentioning
confidence: 99%
See 3 more Smart Citations